Peningkatan Kompetensi Siswa Abad 21 Melalui Kegiatan Pelatihan Dasar Kepemimpinan dan Manajemen Organisasi di MA Unggulan Techno Scientist: Enhancing 21st Century Student Competencies Through Basic Leadership and Organizational Management Training at MA Unggulan Techno Scientist - Sumarsono, Raden Bambang; Sunarni, Sunarni; Kusumaningrum, Desi Eri; Prestiadi, Dedi; Ubaidilah, Endra; Argadinata, Hasan; Setiawan, Wildan Darma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service activity aims to equip and develop the basic leadership and organizational management skills of OSIS (student council) members who are responsible for leading their school organizations, as well as to address the challenges of the 21st century. This community service activity (PKM) was conducted at MA Unggulan Techno Scientist, located in the Karangploso sub-district of Malang Regency, specifically at Jalan Wonokoyo 95, Dusun Boro, Tawangargo Village, Karangploso sub-district, Malang Regency. The distance to the activity location is 16 km, with a travel time of approximately 40 minutes. The training participants consisted of 30 students, including OSIS members and representatives from each class. The supporting instruments for this service included pre-test and post-test sheets. Based on the results of the basic leadership and organizational management training for students at MA Unggulan Techno Scientist in Malang Regency, it can be concluded that the average competency significantly increased to 90.5, with the majority of students (76.67%) falling into the "very good" category. This indicates that the training successfully enhanced the students' leadership and organizational management skills significantly.